Dynamic Modeling of a Six Degree-of-Freedom Flight Simulator Motion Base - Becerra-Vargas, Mauricio [UNESP]; Belo, Eduardo Morgado (ASME International, 2015)
This paper presents a closed-form solution for the direct dynamic model of a flight simulator motion base. The motion base consists of a six degree-of-freedom (6DOF) Stewart platform robotic manipulator driven by electromechanical actuators. The dynamic model is derived using the Newton-Euler method. Our derivation is closed to that of Dasgupta and Mruthyunjaya (1998, Closed Form Dynamic Equations of the General Stewart Platform Through the Newton-Euler Approach, Mech. Mach. Theory, 33(7), pp. 993-1012), however, we give some insights into the structure and properties of those equations, i.e., a kinematic model of the universal joint, inclusion of electromechanical actuator dynamics and the full dynamic equations in matrix form in terms of Euler angles and platform position vector. These expressions are interesting for control, simulation, and design of flight simulators motion bases. Development of a inverse dynamic control law by using coefficients matrices of dynamic equation and real aircraft trajectories are implemented and simulation results are also presented.